Beyond numbers: the role of mathematics self-concept and spatial anxiety in shaping mental rotation performance and STEM preferences in primary education - Lennon-Maslin, Michelle; Quaiser-Pohl, Claudia; Wickord, Lea-Christin (Frontiers in Education, 2024)
Factors such as low self-concept and anxiety adversely affect mathematical achievement and also undermine spatial skills. Enjoyment of maths and related subjects is also compromised. In this crosssectional study, the role of gender, stage of childhood development, maths self-concept, spatial anxiety, perceived difficulty, mental rotation performance and STEM preferences are examined in a sample of 144 primary school students (mean age M=8.47), including 70 girls and 74 boys. Participants completed a computerized Mental Rotation Task (MRT). Self-report and demographic data were collected via four questionnaires. Results indicate that girls and tweens (9-to-11-year-olds) exhibit lower maths self-concept, affecting their preference for maths as a STEM subject. Girls also demonstrate higher spatial anxiety and perceived difficulty of the MRT compared to boys. Maths self-concept is significantly associated with spatial anxiety and perceived difficulty, but gender is not. Maths self-concept shows marginal effects on students' accuracy on the MRT with evidence of a mediating effect of spatial anxiety. Overall, the findings emphasize the significant role of maths selfconcept in shaping STEM preferences, particularly among girls and tweens, while also serving as a mitigating factor for spatial anxiety and perceived difficulty in spatial tasks among primary school children. Additionally, spatial anxiety may contribute to gender disparities in mathematics and STEM-related domains.